Effect of Module use with Scientific Approach on Archaebacteria and Eubacteria Material applied in Discovery Learning Model on Student Biology Learning Competence - Yossi Lolita (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2020)
The learning process of biology at SMAN 1 Batusangkar has used modules but has not used a scientific approach, so that it fully complies with the demands of the 2013 curriculum. While the models used in the learning process are not fully in accordance with the demands of the 2013 curriculum. 2013, the module can be used with a scientific approach in the Discovery learning learning model in the learning process. The aims of this study is to see the effect of the use of modules with a scientific approach to the material of Archaebacteria and Eubacteria in the Discovery learning learning model on biology learning competencies of students of class X MIPA SMAN 1 Batusangkar on Archaebacteria and Eubacteria. This research is an experimental study with the research design of The Static Group Comparison Design. The results showed that the use of modules with a scientific approach to the material of Archaebacteria and Eubacteria in the Discovery learning learning model did not have a positive effect on the competency of biological knowledge and had a positive effect on the competency of attitudes and biology skills of students.